DEVELOPMENT AND IMPLEMENTATION OF CLUSTER POLICY: RUSSIAN AND INTERNATIONAL PRACTICE - Yu. Vertakova; V. Plotnikov; Yu. Polozhentseva (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The cluster policy is one of popular instruments of state regulation of regional development. Its main advantage – possibility of creation (on the ba-sis of clusters) the “growth poles” in region economy. Feature of process of a clustering of economy both in Russia, and in other countries of the world, is the active role of the state in identification of clusters, maintenance of cluster initiatives, stimulation of their development and carrying out monitoring of efficiency of the clustering processes. As a result of the analysis of cluster policy in the certain countries, two main models of implementation of cluster policy are revealed: dirigisme and liberal. They differ in extent of the state intervention. The cluster policy has to be implemented taking into account specifics of spatial structure of economy of the countries and regions. Studying of experience of various countries allowed to allocate two main directions of modern cluster policy: ascending and descending. The ascending approach concentrates on ensuring effective functioning of the market and elimination of market deficiency. At the descending approach the government establishes regional and national priorities, formulates the stimulat-ing vision for the future. The structure of economy of Russia differs from economies of other countries therefore direct loan of institutes of cluster pol-icy is impossible. It is necessary to select the foreign experience with the use of benchmarking.